Impacto de los buques en el desarrollo sostenible en los puertos (2023)
The impact of ships on sustainable development in ports, such as the case of Buenaventura located in Valle del Cauca, are important attributes of a maritime transport chain. Seaports, as modes of cargo, determine the functioning of the supply chains they serve. A constant process that is observed in world coastal transport. The adequacy of the port structure and its accesses is a prerequisite to maintain a good position for the sustainable development of the port and, consequently, of the entire shipping chain.